Charakterystyka demokracji i humanizmu w spuściznie Janusza Korczaka - Marhaim, Tsipi (Studia Edukacyjne, 2020)
In this article the author discusses the revolutionary and unique democratic-humanistic educational approach of Janusz Korczak (1878-1942), which emphasized the fundamental values of the human being concentrated on children and concerning their rights. The author presents democracy as a societal way of life, as practiced by Korczak, Wilczyńska and Falska. They administered their orphanages democratically, as expressed in Korczak’s writings. Social and moral education is presented through a social lifestyle based on fundamental principles of democratic education in the spirit of Korczak. The article also examines the characteristics of democracy itself in the historical perspective and in relation to Korczak’s democratic and humanistic approach. Humanism and democracy as regulators of social life can be greatly inspiring for teachers, educators and parents involved in the process of child education.